Secretory phospholipase A2 inhibitory activity in Tragia hispida: A novel and promising therapeutic agent for dengue fever - D.V. Dayangi Hemalika; U.G. Chandrika; Ajita M. Abeysekera; Sameera R. Samarakoon; Ananda Wijewickrama; Gathsaurie Neelika Malavige (Phytomedicine Plus)
Background: Tragia hispida, is widely used in Sri Lankan traditional ayurvedic medicine for the treatment of fever and internal bleeding. Dengue hemorrhagic fever (DHF) is a severe form of dengue characterized by vascular leakage and potential fatality. Secretory phospholipase A2 (sPLA2), an inflammatory enzyme, plays a critical role in producing platelet-activating factor (PAF), a key mediator of vascular leak. Elevated sPLA2 activity has been linked to the progression of DHF. Purpose: This study aimed to evaluate the sPLA2 inhibitory activity of T. hispida plant extracts with bee venom and dengue patient serum sPLA2. Methods: sPLA2 inhibitory activity of different fractions of the plant was evaluated by a commercially available sPLA2 assay kit compared to the inhibition caused by the commercially available sPLA2 inhibitor CAY 10590. The butanol soluble fraction (THB) of the aqueous extract of Tragia hispida was characterized by TLC and HPLC. Results: Both the aqueous extract (THA) and THB of T. hispida demonstrated sPLA2 inhibition levels comparable to positive control, CAY 10590. At concentrations of 100 µg/ ml and 200 µg/ ml, THB inhibited sPLA2 activity of bee venom by 59.3 % and 84.9 % respectively. Furthermore, THB exhibited significant inhibition of sPLA2 activity in human serum from dengue patients (n = 31, p < 0.0001) than that exhibited by CAY 10590. Conclusions: These findings highlight the potential of T. hispida, particularly THB, as a promising therapeutic agent for dengue fever by inhibiting sPLA2 activity.